(untitled) (American Journal of Islam and Society, 2001)
The aim of the authors in this book was to provide a supplementary text for studies on gender issues in Islamic societies. Ruggles Fairchild (editor) notes that a more significant aim of the book was to broaden not only the geographical realm but the scope and the time frame of analysis of the studies on gender in Islamic societies. This book examines the implicit economic, social and political influence of elite Muslim women in their respective societies by shedding light on the women’s patronage of architecture, clothing and art. Authors argue that such visible expressions - products of women who were otherwise invisible in society - were, and are, reflective of women’s implicit agency (means of exerting power in society) in ancient Islamic societies. The main premise of the authors is that while women have been absent in the explicit representation (depiction) of art, architecture and society, they have in fact been very much present in the background of these realms of Islamic society. While other studies of gender have emerged from consideration of social, economic and political structures in Muslim societies, few (if at all, argue the authors) have emerged from an examination of "visual arts" or "visual culture" (p. 2). This is the void the book seeks to fill. In this sense this book is very important, as it sheds light on the subtle agency of women in ancient Islamic societies and challenges the stereotypical notion that women were (are) subservient, muted entities in Islamic societies (past or present). In their challenge of the stereotypical view of Muslim women in ancient Islamic societies, the authors also question the ...